2016
DOI: 10.1016/j.expneurol.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine is produced in the rat spinal cord and regulates micturition reflex after spinal cord injury

Abstract: Dopamine (DA) neurons in the mammalian central nervous system are thought to be restricted to the brain. DA-mediated regulation of urinary activity is considered to occur through an interaction between midbrain DA neurons and the pontine micturition center. Here we show that DA is produced in the rat spinal cord and modulates the bladder reflex. We observed numerous tyrosine hydroxylase (TH)+ neurons in the autonomic nuclei and superficial dorsal horn in L6–S3 spinal segments. These neurons are dopamine-β-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 49 publications
7
37
0
Order By: Relevance
“…Indeed, we found that excitatory glutamatergic inputs to the L6/S1 spinal cord are increased with LM11A-31 administration, and also onto TH + cell bodies and fiber projections. These TH + neurons appear to participate in bladder reflex circuitry after SCI, since transneuronal labeling from the bladder wall labeled TH + cells in similar regions to those identified in the current study (30). In addition, 6-hydroxydopamine treatment not only reduced the number of these TH + neurons but also reduced voiding efficiency (30).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Indeed, we found that excitatory glutamatergic inputs to the L6/S1 spinal cord are increased with LM11A-31 administration, and also onto TH + cell bodies and fiber projections. These TH + neurons appear to participate in bladder reflex circuitry after SCI, since transneuronal labeling from the bladder wall labeled TH + cells in similar regions to those identified in the current study (30). In addition, 6-hydroxydopamine treatment not only reduced the number of these TH + neurons but also reduced voiding efficiency (30).…”
Section: Discussionsupporting
confidence: 69%
“…After SCI, many of these fiber projections appeared lost ( Figure 7D), and instead a distinct group of neurons emerged with clear cell soma morphology in the area of the DCM, expressing both p75 and TH. In accordance with these data, modulating dopamine production has recently been shown to influence micturition after SCI (30).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…A total of 6 µL of PRV‐152 (Bartha strain, 10 9 pfu/mL, courtesy of Dr. Michael A. Lane), encoding for green fluorescent protein (GFP), was injected into the bladder detrusor at three different sites, including the front, and bilateral sides, 2 µL per site, with a 10 µL Hamilton syringe connected with a fine glass tip . Injection sites were immediately sealed with a small drop of tissue glue.…”
Section: Methodsmentioning
confidence: 99%
“…This might be due to that the detecting techniques used in related studies were not sensitive enough to disclose a small amount of 5-HT, or the turnover rate of 5-HT produced in the AADC cells was so high that once produced it was immediately metabolized. One piece of evidence to support the speculation that monoamine transmitters could be produced from AADC cells in the spinal cord after SCI comes from Hou et al [199], who showed that the number of dopamine-producing cells, which contained both AADC and tyrosine hydroxylase, was increased in lumbosacral spinal cord in thoracic spinal transected rats; and with enzyme-linked immunosorbent assay (ELISA) dopamine with a content of about 10% of its normal value could be detected in this part of the spinal cord even without L-dopa applica-tion. At the same time they also showed that dopamine produced from the spinal cord below the lesion was implicated for micturition functional recovery following SCI.…”
Section: Plasticity Of 5-ht Innervations After Scimentioning
confidence: 99%